Identification of Early Temperament Profiles in Infants at Elevated Likelihood for Autism and Attention-Deficit/Hyperactivity Disorder - Girija Kadlaskar; Ana-Maria Iosif; Sally Ozonoff; Meghan Miller (Clinical Psychological Science, 2026)
Autism and attention-deficit/hyperactivity disorder (ADHD) likely share some common developmental pathways, suggesting the potential for overlapping early risk factors, including aspects of temperament. We employed a transdiagnostic, data-driven approach to identifying temperament-based subgroups at 12 and 18 months across infants at elevated and low genetic likelihood for autism and ADHD. Results revealed general continuity in early temperament; many infants remained in a well-regulated/socially engaged subgroup (73%), and some (27%) showed shifts over time toward heightened negative reactivity, greater inhibition, and/or reduced social engagement during the toddler period. Not all infants/toddlers who later met criteria for autism or showed preschool concerns for ADHD demonstrated negative-reactive/inhibitory temperament traits during early development. However, certain temperament profiles were associated with autism and ADHD traits regardless of clinical outcome. Findings contribute to a better understanding of early transdiagnostic markers and the nuanced developmental pathways related to autism and ADHD.